POLA KOMUNIKASI ANTAR REMAJA DI ERA DIGITAL DI DESA SERUMPUN KECAMATAN SALATIGA - Hesti Komah; Rustiyarso Rustiyarso; Izhar Salim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThe title of this thesis is The Communication Pattern Among Adolescents in the Digital Era in Serumpun Village Salatiga District. This research is using qualitative approach with descriptive method. The data collecting tools used is the observation guidelines, interview guideline and documentation study. The general research result shows that there is a shift in the comunal communication into individuals. Communication patterns that are established through digital media result in adolescents making grouped friendship because of the same goals and desires. The pattern of communication between adolescents is predominantly using a multi-way communication carried out using media that penetrates the space of time and allows youth to communicate silmutaneously and countinously. While the results of special studies indicates that:(1) the type of social media used by the adolescents to communicate in the digital era is facebook, whatsapp, instagram, line, messenger.(2) the conversation content between teenager based on the same eagerness and function such as the conversation about sport, hoby and school. (3) as for the positive effect of the use of communication media in the digital era is: facilitate the communication process, the communication also can be done anywhere at any time, cost effective. Negative effect: raises the attitude of individualism, addicted to smart phone, reduced direct interaction (face to face). Keywords : Adolescents, Communication Pattern, Digital Era.